Influence of Self Consciousness, Religious Dependence and Culture on Family Planning among Health Educators in Public Secondary Schools in Bayelsa and Delta States - Okudaye, I. N. (Advances in Social Sciences Research Journal, 2025)
This study was undertaken to investigate influence of self consciousness, religious dependence and Culture on family planning among health educators in public secondary schools in Bayelsa and Delta states. The design adopted in this study was descriptive survey design. The population was 332 married health educators in public secondary schools in Bayelsa and Delta states. The population was 119 married health educators in 163 public secondary schools in Bayelsa and 213 married health educators in 649 public secondary schools in Delta state in 2020/2021 academic year. The researcher sampled the entire 332 health educators in Bayelsa and Delta states public secondary schools because of their fewness. The questionnaire used in this investigation was described as Self Consciousness, Religious Dependence, Culture and Family Planning Questionnaire (SCRTFPQ). Out of 332 questionnaires administered 309 were returned. Married health educators in Bayelsa state public secondary schools was 107 while married health educators in Delta states public secondary schools was 202. Items on the questionnaire were assessed with the four point’s assessment scale varying from Strongly Agree (4 points), Agree (3 points), Disagree (2 points) and Strongly Disagree (1 point). Mean rating and standard deviation were utilised to respond on the three research questions. z test Statistics was utilised to examine the 3 null hypotheses formulated to direct the investigation at 0.05 levels of significance. Findings showed that influence of self consciousness and family planning among health educators in public secondary schools in Bayelsa and Delta states were high as the ratings were high. That the influence of religious dependence , culture and family planning among health educators in public secondary schools in Bayelsa and Delta states were low as the ratings were low. That there was no significant difference on the influence of self consciousness and family planning among health educators in Bayelsa and Delta states. That there was significant difference on the influence of religious dependence, culture and family planning among health educators in public secondary schools in Bayelsa and Delta states. It was concluded in the study that that self consciousness influence family planning among health educators in public secondary schools in Bayelsa and Delta states were high. That religious dependence, culture do not influence family planning among health educators in public secondary schools in Bayelsa and Delta states were low as the ratings were low. That self consciousness does not significantly differ on the influence of family planning among health educators in Bayelsa and Delta states. That religious dependence, culture significantly differs on the influence of family planning among health educators in public secondary schools in Bayelsa and Delta states. It was recommended among other that health educators in public secondary schools in Bayelsa and Delta states should ensure that they use their self consciousness in family planning.